An endogenous human peptide derived from α1-antitrypsin as a novel pharmacological inhibitor of Bordetella pertussis toxin - Lietz, Stefanie; Sokolowski, Lena-Marie; Beyschlag, Alexander; Rosenau, Helena; Siewert, Annika; Alfonso, Armando A. Rodríguez; Preising, Nico; Ständker, Ludger; Wiese, Sebastian; Köhler, Janet; Weidinger, Gilbert; Münch, Jan; et al. (Springer Science and Business Media LLC, 2026)
Pertussis, also known as whooping cough, is a highly infectious respiratory disease caused by the bacterium Bordetella pertussis. The bacterial virulence factor, pertussis toxin (PT), is associated with the manifestation of the characteristic symptoms of pertussis and the severe form of this disease. Increasing case numbers and the lack of treatment options highlight the need to develop novel pharmacological strategies, e.g., the generation of specific PT inhibitors. Recently, we identified the endogenous human protein alpha(1)-antitrypsin (alpha(1)AT) as an inhibitor of PT from a screening of a human hemofiltrate protein/peptide library. In the present work, we tested an in-house alpha(1)AT peptide bank to identify an alpha(1)AT region with anti-PT activity. Then, we compared the sequences of the positive hits from the peptide bank with all known alpha(1)AT fragments in the hemofiltrate samples to find new active peptides. In total, 36 peptides were tested for their PT inhibition, leading to the identification of an endogenous alpha(1)AT fragment, alpha(1)AT HF, derived from hemofiltrate with anti-PT activity. This peptide had no toxic effects on HeLa cells and in vivo on zebrafish embryos, rendering it an attractive lead compound for further evaluation to treat pertussis in the future.